Graphene plasmonics and metamaterials - Li, Qiuyu (2019)
As a novel transform optics, hyperlens is a promising real-time high-resolution lens that efficiently converts evanescent waves into traveling waves, breaking the diffraction limit that has a negative impact in the optical field. So far, there are two ways to realize hyperlens. One is to design and implement hyperlens by using the negative dielectric constant of metals in the optical frequency band, the other is to use the stacking structure of layered metals and dielectrics to equivalent the heterogeneous medium different from the natural material. However, due to the loss, the imaging efficiency of these designs is not high. Graphene and hexagonal boron nitride are emerging two-dimensional planar materials, which have caused great research boom due to the existence of many novel electrical and optical properties. Therefore, in this thesis, we use FDTD to simulate an 2D structure, which made by graphene, hBN, Au and Si. Firstly, by chaging the thickness of hBN from 100nm to 600nm, the electric field distribution with respect to the thickness and wavelength were obseved. It was found that the magnification increased linearly with the thickness of hBN. Through linear fitting, the relationship between them is obtained as follows: Δ=2.013d. Next, we adjusted the Fermi level of graphene from 0.1eV to 1eV, observing the distribution of the electric field component (Ey) in the y direction. The results show that as the graphene Fermi level increases, the amplification distance of Au on the graphene surface is shorter due to the particularity of its band structure. These results provide a useful basis for further design of metamaterial-based lenses, enabling control of lens magnification.